2018
DOI: 10.12783/dtssehs/amse2018/24837
|View full text |Cite
|
Sign up to set email alerts
|

Modified Artificial Bee Colony Algorithm for the Capacitated Vehicle Routing Problem

Abstract: We propose an improved artificial bee colony algorithm to solve CVRP. Inspired by genetic algorithm and particle swarm optimization, the enhanced ABC algorithm uses the information of the optimal solution of the current population, current individual and the historical optimal information of current individual to update the individuals. The performance of the proposed algorithm is tested on CVRP instances and compared with the state-of-the-art algorithms. Results show that the algorithm is effective and feasib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…As a variant of VRP problem, our work is an inherently non-deterministic polynomial (NP-hard) problem, which need to be addressed by heuristic algorithms, such as particle swarm optimization algorithm [44]- [46], genetic algorithm [47], [48], artificial bee colony algorithm [49], [50], fruit fly optimization algorithm [51], [52], tabu search algorithm [53], [54], simulated annealing algorithm [55], [56], The ant colony optimization (ACO) algorithm was first proposed by Dorigo et al [57], it has shown good performance in solving problems such as task assignment and route optimization. The advantages of ACO in real applications have also been demonstrated [58]- [60].…”
Section: B Research On Route Scheduling Optimizationmentioning
confidence: 99%
“…As a variant of VRP problem, our work is an inherently non-deterministic polynomial (NP-hard) problem, which need to be addressed by heuristic algorithms, such as particle swarm optimization algorithm [44]- [46], genetic algorithm [47], [48], artificial bee colony algorithm [49], [50], fruit fly optimization algorithm [51], [52], tabu search algorithm [53], [54], simulated annealing algorithm [55], [56], The ant colony optimization (ACO) algorithm was first proposed by Dorigo et al [57], it has shown good performance in solving problems such as task assignment and route optimization. The advantages of ACO in real applications have also been demonstrated [58]- [60].…”
Section: B Research On Route Scheduling Optimizationmentioning
confidence: 99%
“…In previous studies, several types of meta-heuristic algorithms have been carried out to solve CVRP, including Simulated Annealing [7], Genetic Algorithm [8], Particle Swarm Optimization [9], Firefly Algorithm [14], and Artificial Bee Colony [15] [16]. Based on these studies, Artificial Bee Colony (ABC) is one of the meta-heuristic algorithms that can produce the best average solution output.…”
Section: Introductionmentioning
confidence: 99%